Pengaruh Kepemilikan Institusional dan Leverage Terhadap Tax Avoidance dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi (Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Nahat, Leonita Yulianti Anur; Yoshida, Debbie (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this study is to test and collect empirical data on the influence of Tax Avoidance on Institutional Ownership, Leverage, and Company Size. The independent variables of this study are Institutional Ownership and Leverage. Tax Avoidance serves as the dependent variable of the study, and Company Size serves as the moderating variable. Secondary data used in this study are sourced from the official website of the Indonesia Stock Exchange (IDX) and the websites of each company. The population of this study consisted of 92 property and real estate companies listed on the IDX from 2020 to 2023, with the Purposive Sampling technique used and a sample of 18 companies listed on the property and real estate Company on the IDX. The data analysis of this study used descriptive statistical analysis with the help of SPSS version 25. The results of the study indicate that Institutional Ownership and Leverage has a negative effect on Tax Avoidance. Company Size does not have a moderating effect on the relationship between Institutional Ownership and Leverage with Tax Avoidance.